BIODEGRADATION OF PHENOL BY NATIVE MICROORGANISMS ISOLATED FROM LONAR LAKE IN MAHARASHTRA STATE (INDIA): Pharmaceutical Science-Environmental Microbiology - TAMBEKAR D. H.; P.S. BHORSE; P.V GADAKH (International Journal of Life Science and Pharma Research, 2012)
The present study was aimed to isolate phenol degrader from Lonar Lake situated in Buldhana district of Maharashtra state, India, ranks third in the world based on diameter and its high alkalinity (pH 10.5). From 4 sediments and water samples of Lonar Lake, a bacterium Pseudomonas stutzeri was isolated and identified based on morphological, cultural, biochemical properties and 16S rRNA gene sequencing. Our experiment showed that the isolate removes almost 87% phenol in the peptone water-phenol medium at laboratory level. Thus, the alkaliphilic bacterium, Pseudomonas stutzeri, ensuring an acceptable Lonar lake bacterium, which could therefore be commercially exploit for bioremediation of phenol, a major toxic pollutant in industrial waste effluents.